The Impact of Beta-Lactam Antibiotics on Bacterial Infection Prevalence and Socioeconomic Determinants in Middle-Aged Adults Across Three West African Countries - Kelechi, Dilaku Joseph (European Journal of Applied Sciences, 2024)
This research is to ascertain the impact of Beta-lactam classes of antibiotics on the prevalence of bacterial infections, and the socioeconomic determinants influencing their usage in the middle-aged adults within (35-50) years, across diverse populations of some West African countries. The investigation provides insights into how antibiotics use varies by socioeconomics factors such as access to healthcare, education, income level and its later effect on health outcomes. This study utilizes the mix of quantitative analysis via survey questionnaire and qualitative analysis through interviews and focus group of patients. It was used to collect data from 3300 middle-aged adults across three West African countries to understand the prevalence of bacterial infections, and socioeconomic factors influencing the usage of the aforementioned classes of antibiotics. This mixed-methods approach was employed, combining quantitative analysis (descriptive, regression, and multivariate analysis using Real Statistics v2 in Excel) with qualitative thematic analysis of interviews and focus group data using taguette software.Triangulation was also used to validate findings and provide a comprehensive understanding of the research problem. Quantitative data revealed that socioeconomic factors significantly impact antibiotic use, with financial constraints and limited healthcare access correlating with increased self-medication and misuse. Cronbach’s Alpha indicated high internal consistency across survey responses. Thematic analysis identified key themes, including cost as a barrier to healthcare, the role of policies in antibiotic use, and awareness of antibiotic risks. Participants expressed concerns about antibiotic resistance and the quality of available medications, highlighting the growing issue of ineffective drugs. The study emphasizes the need for health policy reforms, drug regulation, and interventions that integrate education with economic support to promote responsible antibiotic use. Future research should focus on long-term trends in antibiotic resistance, the role of pharmacies, and interventions targeting both system-level and behavioral factors.